Visibility beyond the visible - Bakracheva, Albena (Rodopi, 2013)
Preliminary Material /Bakratcheva Albena – THE NEW ENGLAND IDENTITY OF THE TERM /Bakratcheva Albena – PURITANISM AND EIGHTEENTH-CENTURY RATIONALISM /Bakratcheva Albena – UNITARIANISM AND TRANSCENDENTALISM /Bakratcheva Albena – THE EMPHASIS ON INSPIRATION IN TRANSCENDENTAL AESTHETICS /Bakratcheva Albena – TRANSCENDENTALISM: POETIC-RELIGIOUS PRACTICE AND WAY OF LIFE /Bakratcheva Albena – THE NEW ENGLAND HORIZONS OF POST-KANTIANISM: EMERSON /Bakratcheva Albena – THE VISION OF THE NEW ENGLAND TRANSCENDENTALIST: THOREAU /Bakratcheva Albena – THE ENCHANTMENT OF THE VOYAGE BACK: MARGARET FULLER /Bakratcheva Albena – TRADITIONS AND INDIVIDUAL TALENT: EMERSON AND THOREAU /Bakratcheva Albena – LIFE AS VOCATION /Bakratcheva Albena – HOMOCENTRISM AND ECOCENTRISM /Bakratcheva Albena – BIBLIOGRAPHY /Bakratcheva Albena – INDEX /Bakratcheva Albena. Visibility beyond the Visible. The Poetic Discourse of American Transcendentalism is the first study to entirely deal with the poetics of American Transcendentalism. The author takes it for granted that the major New England transcendentalists were writers of utmost literary significance and so focuses thoroughly on their extremely rich and many-sided poetic discourse. The book’s inevitable European perspective only enhances its preoccupation with the Americanness of the New England Transcendentalists, thus making it emphasize, in all the aspects of its concern, the uniqueness of the interrelation between place-sense and artistry which the transcendentalists’ writings offer. Because most of these writings hold iconic stature as American masterpieces, both scholars and lay readers will welcome Visibility beyond the Visible. The Poetic Discourse of American Transcendentalism as opening novel horizons for greater insights, deeper understandings, and further exploration of the poetic complexities of Emerson’s, Thoreau’s, M. Fuller’s, and their co-thinkers’ work
10.1163/9789401208314
Keywords: American literature; Transcendentalism in literature; Transcendentalism (New England); Criticism; interpretation; etc